Lived Experiences and Challenges of Multigravida Women with Gestational Diabetes Mellitus - Naeem, Sonia; Amjad, Sibra (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVES: The current research aimed to explore the lived experiences and challenges of the multigravida women with GDM. METHODOLOGY: Qualitative research design, with use of Phenomenological Approach was used. Semi-structured interview technique was employed to collect firsthand data from multigravida, on their experiences and challenges of pregnancy with GDM. A purposive sample of five participants were recruited from different hospitals in Lahore, with the age range between 25 to 35 years. After the collection of data, the interviews were transcribed and the data was analyzed through interpretative phenomenological analysis. RESULTS: This results of the study highlights the multifaceted challenges faced by multigravida women with GDM, including emotional and physical burdens, mental health impacts, and difficulties in adhering to dietary and medical recommendations. It also sheds light on the coping strategies women adopt and the critical role of family and social support systems. Additionally, regular glucose monitoring and education emerged as essential components for managing GDM and ensuring a healthy pregnancy. Among these, disrupted mental health and the coping of GDM stood out as the most significant. CONCLUSION: These findings underscore a holistic approach in GDM care—one that not only addresses medical management but also prioritizes psychological support and leverages social and spiritual resources. By highlighting these issues the study will be beneficial to raise awareness among women and professionals about the importance of dietary guidance, emotional well-being, social support and self-management, ultimately contributing to improved maternal care and better fetal health outcomes.